2019
DOI: 10.1016/j.dib.2019.103775
|View full text |Cite
|
Sign up to set email alerts
|

Data of clavulanic acid and clavulanate-imidazole stability at low temperatures

Abstract: Clavulanic acid (CA) is a β-lactam antibiotic with a strong inhibitory effect on β-lactamase enzymes. CA is produced in submerged cultures by the filamentous Gram-positive bacterium Streptomyces clavuligerus (S. clavuligerus). CA is an unstable molecule in aqueous solution and its stability depends strongly on temperature and concentration. In this contribution, the experimental data of CA stability, produced in chemically defined media and exposed to temperatures between −80 and 25 °C, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
0
5
0
1
Order By: Relevance
“…CA is usually produced in submerged cultures under appropriate nutritional conditions. However, CA is unstable in aqueous solutions including fermentation broths and its productivity is compromised in both production and downstream processes [ 2 , 3 ]. Several studies have focused on assessing the effect of nutrients and environmental conditions on CA production and have identified a variety of operational conditions that presumably favor its accumulation during the cultivation process, as previously reviewed by Ser et al [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…CA is usually produced in submerged cultures under appropriate nutritional conditions. However, CA is unstable in aqueous solutions including fermentation broths and its productivity is compromised in both production and downstream processes [ 2 , 3 ]. Several studies have focused on assessing the effect of nutrients and environmental conditions on CA production and have identified a variety of operational conditions that presumably favor its accumulation during the cultivation process, as previously reviewed by Ser et al [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Shear conditions in CA production has been previously explored in airlifts [3] and stirred tank reactors [4]; however, the physiological response of S. clavuligerus to shear forces and its relationship with CA secretion is not completely understood. Many efforts have been carried out to increase the yield of CA since not only nutritional, but also environmental and degradation factors compromise the product yield in submerged cultivations of S. clavuligerus [5,6]. Several studies focused on the effect of nutrient concentrations and environmental cultivation conditions on CA biosynthesis, as Ser et al [7] reviewed.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have confirmed the degradation of CA in fermentation broths [67,69,[168][169][170], synthetic buffer [68,171,172], and pure water [173][174][175]. The CA secreted by S. clavuligerus exhibits a high initial reaction rate (~5 h) in aqueous solution (e.g., fermentation broths) followed by a slower degradation rate in the next hours [168,169]. Degradation of CA is considered consequence of susceptibility to nucleophilic attacks at specific points.…”
Section: Downstream Processing Of Camentioning
confidence: 99%
“…In addition to the characteristic low productivity of the bioprocess, the product yield is also compromised by the degradation of CA in aqueous phases and the efficiency of the separation steps required for the obtention of potassium clavulanate (the stable commercial form). Several authors have confirmed the degradation of CA in fermentation broths [ 67 , 69 , 168 , 169 , 170 ], synthetic buffer [ 68 , 171 , 172 ], and pure water [ 173 , 174 , 175 ]. The CA secreted by S. clavuligerus exhibits a high initial reaction rate (~5 h) in aqueous solution (e.g., fermentation broths) followed by a slower degradation rate in the next hours [ 168 , 169 ].…”
Section: Downstream Processing Of Camentioning
confidence: 99%